Effective Leadership Styles for the Modern Workplace - Chakraborty, Archita; Banerjee, Srikrishna (International Journal of Advances in Business and Management Research (IJABMR), 2023)
A proficient leader exerts influence on their followers in a desirable way to accomplish goals and objectives. The research clearly indicates that various leadership styles may impact an organization’s efficacy and performance. The evolution of many leadership styles across time. The information was acquired via a comprehensive assessment of several articles, research papers, and publications on various leadership styles from a range of reputable journals, periodicals, and books. Furthermore, the study suggests that the significance of both transactional and transformational leadership models has increased due to the extensive research conducted in these areas. A successful leader exerts influence on followers, guiding them towards the attainment of goals and objectives. The research indicates that various leadership styles may influence the efficacy and efficiency of a corporation. A systematic and comprehensive analysis of existing literature and research constitutes the methodology employed in this review paper. Various forms of leadership have evolved over time. The knowledge has been acquired via extensive reading of several articles and research papers on leadership styles, as well as a wide range of publications, journals, and books. Also, a lot of research has shown that both transformational and transactional styles of leadership are more important because they are directly related to how leaders do their jobs and because a lot of research has been done on them.